A cosmogenic view of erosion, relief generation, and the age of faulting in southern Africa - Bierman,PR; Coppersmith,R; Hanson,K; Neveling,J; Portenga,EW; Rood,DH (GSA Today, 2014)
Southernmost Africa, with extensive upland geomorphic surfaces, deep canyons, and numerous faults, has long interested geoscientists. A paucity of dates and low rates of background seismicity make it challenging to quantify the pace of landscape change and determine the likelihood and timing of fault movement that could raise and lower parts of the landscape and create associated geohazards. To infer regional rates of denudation, we measured10Be in river sediment samples and found that south-central South Africa is eroding ∼5 m m.y.-1, a slow erosion rate consistent with those measured in other non-tectonically active areas, including much of southern Africa. To estimate the rate at which extensive, fossil, upland, silcrete-mantled pediment surfaces erode, we measured10Be and26Al in exposed quartzite samples. Undeformed upland surfaces are little changed since the Pliocene; some have minimum exposure ages exceeding 2.5 m.y. (median, 1.3 m.y.) and maximum erosion rates of <0.2 m m.y.-1(median, 0.34 m m.y.-1), consistent with no Quaternary movement on faults that displace the underlying quartzite but not the silcrete cover. We directly dated a recent displacement event on the only recognized Quaternary-active fault in South Africa, a fault that displaces both silcrete and the underlying quartzite. The concentrations of10Be in exposed fault scarp samples are consistent with a 1.5 m displacement occurring ca. 25 ka. Samples from this offset upland surface have lower minimum limiting exposure ages and higher maximum erosion rates than those from undeformed pediment surfaces, consistent with Pleistocene earthquakes and deformation reducing overall landscape stability proximal to the fault zone. Rates of landscape change on the extensive, stable, silcretized, upland pediment surfaces are an order of magnitude lower than basin-average erosion rates. As isostatic response to regional denudation uplifts the entire landscape at several meters per million years, valleys